Preserved egg white alleviates DSS-induced colitis in mice through the reduction of oxidative stress, modulation of infl ammatory cytokines, NF-κB, MAPK and gut microbiota composition - Lingyu Li; Ning Qiu; Yaqi Meng; Chenyan Wang; Yoshinori Mine; Russell Keast; Vincent Guyonnet (Food Science and Human Wellness)
Traditional Chinese preserved egg products have exhibited some anti-inflammatory effects, but their mechanisms of action remain unknown. This study aimed to investigate the anti-inflammatory effects of preserved egg white (PEW) treatment on dextran sulfate sodium (DSS)-induced colitis in mice and the underlying mechanisms. The results showed that treatment with PEW in mice with DSS-induced colitis for 14 days effectively improved the clinical signs, inhibited the secretion and gene expression of pro-inflammatory cytokines, and reduced myeloperoxidase (MPO) activity and oxidative stress levels. In addition, western blotting results showed that PEW significantly suppressed DSS-induced phosphorylation levels of nuclear factor-kappa B (NF-κB) p65 and p38 mitogen-activated protein kinase (MAPK) in colon tissues of mice with colitis. PEW also enhanced the production of short-chain fatty acids (SCFAs) and modulated gut microbiota composition in mice with DSS-induced colitis, including increasing the relative abundance of beneficial bacteria Lachnospiraceae, Ruminococcaceae and Muribaculaceae, and reducing the relative abundance of harmful bacteria Proteobacteria. Taken together, our study demonstrated that preserved egg white could alleviate DSS-induced colitis in mice through the reduction of oxidative stress, modulation of inflammatory cytokines, NF-κB, MAPK and gut microbiota composition.